UPAYA INDONESIA MENINGKATKAN EKSPOR FURNITUR KE AMERIKA SERIKAT DI TENGAH PERANG DAGANG AMERIKA SERIKAT-CHINA - Zainal Abidin; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia is bestowed on vast areas for timber production. Furniture industries can get various raw materials for exporting products. The United States of America, China, and European Union are the potential market. Trade war between the USA and China enable Indonesia to improve its export to the USA. This phenomena intrigued researcher to describe Indonesian effort to boost its export to USA. Domestic barriers in Indonesia and the measures to improve the export will be described in-depth.Data come from secondary sources such as books, journals, news from magazines and newspapers, official documents from Indonesian governments, and websites. This documents will be analyzed to answer effective measures to boost export to the USA. Perspective of mercantilism, the level of analysis of the nation state and the theory of economic diplomacy will be utilized to describe the efforts. The research showed that Indonesian government and furniture associations play important role in improving the performance of the Indonesian’s furniture industry. Policies undertaken to increase US furniture exports include improving the quality of human resources through training, improving technology, lowering interest rates for loan, and increasing the quality and standardization of furniture. Promotion of national and international furniture products through exhibition as well as cooperation with IKEA is also carried out to improve and introduce furniture products to the world, especially in the United States.Keywords: Export, Furniture, Association of Indonesian Furniture and Handicraft Industry (HIMKI), Indonesia, United States.